PENGARUH PENGETAHUAN AKUNTANSI DAN PENGALAMAN USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM(Studi Empiris Pada UMKM Dikota Ambon) - Iren Natalia Mahudin; Linda Grace Loupatty (BORJUIS: JURNAL OF ECONOMY, 2025)
This research aims to empirically test the influence of accounting knowledge and business experience on the use of accounting information in Micro, Small and Medium Enterprises (MSMEs) in Ambon City. This research is a type of quantitative research. The data used is primary data collected through survey techniques using questionnaires. The sample obtained was 100 respondents from micro business actors in Ambon City. Data analysis uses multiple regression analysis tools, with the variables tested being accounting knowledge (X1), business experience (X2) and use of accounting information (Y). The research results show that the variables accounting knowledge and business experience have a significant positive effect on the use of accounting information.